Ethical Dilemma in Giving Auditor Opinions: A Review Based on Principle Theory - Jihad Agil Maulana Kusuma Jihad; Driana Leniwati (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
This study aims to examine the provision of audit opinions based on virtuous ethics theory in facing ethical dilemmas at a Public Accounting Firm in Malang. This study uses a qualitative approach with purposive sampling. The research informants consisted of four auditors: a partner, a senior auditor, and a junior auditor. Data collection techniques were conducted through in depth interviews, observation, documentation and data triangulation. Data analysis techniques used the Miles, Huberman, and Saldana model through the stages of data reduction, data presentation and conclusion drawing. The results show that virtuous theory is related to the auditor's professional code of ethics. Honesty relates to integrity, fairness relates to objectivity and independence while trustworthiness relates to competence, confidentiality and professional behavior. Auditors face ethical dilemmas in maintaining honesty and independence when providing audit opinions. This study concludes that the auditor's moral character is an important foundation for maintaining the quality of the audit opinion and increasing public trust in the audit profession